Optimización del proceso de extracción hidroalcohólica a partir del Cedrón (aloysia citrodorae paláu) en función de polifenoles totales y actividad antioxidante. - Maldonado Toapanta, Natali Manuela (2021)
This research study was based on the improvement of the hydroalcoholic extraction process of lemon verbena leaves (Aloysia citrodora paláu) depending on the content of total polyphenols and antioxidant activity, analyzing their phytochemical characteristics, in order to obtain updated and verified information on the bioactive compounds. The lemon verbena was harvested before its flowering, since in its young stage there is a higher concentration of bioactive compounds. Subsequently, 1g of crude drug was used to obtain each extract using solvents of different polarities; Those which underwent phytochemical screening, in order to qualitatively know their bioactive compounds, the presence of fatty compounds, steroids, catechins, reducing sugars, saponins, phenolic compounds, quinones, flavonoids, mucilages and bitter bioactive compounds. The experimental runs were developed through the Design Expert 8.0.6 program in which 23 runs were carried out with three factors such as ethanol concentration (60%, 75% and 90%), time (6h, 15h and 24h) and temperature (30 °C and 60 °C). The content of total polyphenol and antioxidant capacity of each experimental run were determined. By increasing ethanol concentration, time and extraction temperature, the content of total polyphenols and antioxidant capacity of the hydroalcoholic extracts of the crude drug of lemon verbena leaves were increased. The optimized hydroalcoholic extract presented 0.28 mg EAG / g of total polyphenols and 909.36 uM of Fe2 + / g of antioxidant capacity, this being a higher value than that obtained by numerical optimization.